Analysis on PT Semen Indonesia Organizational Culture Based on Organizational Cultural Assessment Instrument (OCAI) - Zulfikar, Rachmat Calief; Gustomo, Aurik (Journal of Business and Management, 2014)
Up until now, PT. Semen Indonesia has been dominating the cement industry competition in Indonesia. In the other sides, the South East Asia region will encounter a new phenomenon in 2015 which is ASEAN Economic Community (AEC) with the mission of making ASEAN region as a region with free movement of goods, services, investment, skilled labor, and a free flow of capital, that have the program of improving the implementation of ASEAN Free Trade Area (AFTA) which will eliminate any cost of tariff for goods trading from any ASEAN region countries. That means the competition that PT. Semen Indonesia will encounter is not only against other Indonesian private companies, but also with other ASEAN countries’ companies. This research’s objectives is to assess the current condition of PT. Semen Indonesia’s organizational culture and also the preferred organizational culture by PT. Semen Indonesia’s employees by using Organizational Culture Assessment Instrument (OCAI. The result shows that the current organizational culture in PT. Semen Indonesia is balanced without any tendency to any category of organizational cultural framework. While for the preferred condition by PT. Semen Indonesia’s employees, the culture tends to Entrepreneurial and Clan Culture.Keywords: Semen Indonesia, Organizational Culture, OCAI, AEC, AFTA